(untitled) (Eurasian Journal of Humanities and Social Sciences, 2023)
The study of above mentioned subject on the basis of national mentality is an initial step in the years of Independence of Uzbekistan. Because, such a positive approach to the sources of spiritual values, if on the one hand, helps to feel initial oneness of mankind noted in divine messages; on the other hand, it creates mutual understanding among the nations with different faiths, which is important today in struggling against the international extremism and terrorism. By the way, «All religions», - as a well-known sufi Mansoor Khallaj said, - «are the different twigs of one and the same Tree.» In accordance with this view-point, in our investigation we tried to continue the tradition of Abu Reikhan Beruni, who over a thousand years ago created the scientific method of comparative study of the world national values – history, religions, culture and traditions